2017
DOI: 10.15344/2456-4028/2017/119
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone Resistance Detection by PCR-RFLP and Multiplex-PCR among Extended- Spectrum β- Lactamase Producing Enterobacteriaceae

Abstract: Quinolone resistance limits the therapeutic potential for the Extended-Spectrum β-lactamase (ESBL) producing Enterobacteriaceae. The aim of this study was to investigate the most common mechanisms of quinolones resistance in ESBL-producing Enterobacteriaceae using both phenotypic and genotypic methods. Out of 1766 clinical isolates collected between October 2012 and September 2013, 219 Enterobacteriaceae clinical isolates were ESBL producers, nalidixic acid and ciprofloxacin resistant were identified by Matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…16 High prevalence of PMQR determinants was also reported by El-sayed Marei et al among both extended-spectrum beta-lactamases (ESBLs) and non-ESBLs producing Enterobacteriaceae isolates (93.1% and 76%, respectively) from UTI. 31 In another study carried out by Khalil et al, a prevalence of PMQR genes of 85.7% was found among ESBLs producing Enterobacteriaceae clinical isolates, with aac(6ʹ)-Ib-cr gene being the most prevalent (72.7%), followed by qnr genes (39.3%), 32 which comes consistent with our result.…”
Section: Discussionsupporting
confidence: 90%
“…16 High prevalence of PMQR determinants was also reported by El-sayed Marei et al among both extended-spectrum beta-lactamases (ESBLs) and non-ESBLs producing Enterobacteriaceae isolates (93.1% and 76%, respectively) from UTI. 31 In another study carried out by Khalil et al, a prevalence of PMQR genes of 85.7% was found among ESBLs producing Enterobacteriaceae clinical isolates, with aac(6ʹ)-Ib-cr gene being the most prevalent (72.7%), followed by qnr genes (39.3%), 32 which comes consistent with our result.…”
Section: Discussionsupporting
confidence: 90%
“…PMQR was detected in 36/43 (83.72%) phenotypically fluoroquinolone-resistant isolates. Several studies showed similar results [ 39 , 40 ]. Other studies that investigated PMQR genes recorded variations in their prevalence rate even in the same country [ 41 44 ].…”
Section: Discussionsupporting
confidence: 56%
“…In previous studies, integron I was more frequent among Gram-negative bacteria [36][37][38]. [39,40]. Other studies that investigated PMQR genes recorded variations in their prevalence rate even in the same country [41][42][43][44].…”
Section: Discussionmentioning
confidence: 94%
“…Similar to findings reported by Khalil, et.al. [ 55 ], we found that PaβN, as an efflux pump inhibitor, reduced the ciprofloxacin MIC in isolates containing OqxA/B supporting the importance of OqxA/B in ciprofloxacin resistance. It has been shown that the coexistence of PMQR determinates in E. coli could potentially cause higher levels of quinolone resistance [ 50 ].…”
Section: Discussionsupporting
confidence: 56%